ARE CRUDE OIL PRICE AND EXCHANGE RATE REALLY MAJOR CAUSES OF THE MOVEMENT IN THE THAI RETAIL GASOLINE PRICE? - Pamornpathomkul, Santikorn; Chaimongkol, Nartraphee; Jeambua, Katawoot (RMUTT Global Business and Economics Review, 2015)
This paper uses daily data to analyze the correlation between the Thai retail gasoline price to the change in crude oil price and exchange rate during the period of August 2006 to November 2014. The conclusions from the OLS estimation show that both crude oil price and exchange rate are, but not only, the causes of the movement in retail prices of ULG 95 RON in Bangkok. The seasonal factor might need to be considered for the unit change of gasoline price rather than the percentage change. Furthermore, some of the government charges are also major causes with almost 100% pass-through effect on the movement of the Thai retail gasoline price.